2001
DOI: 10.1089/104303401750061230
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment of Autologous Retrovirally Transduced Hepatocytes after Intraportal Transplantation into Nonhuman Primates: Implication forex VivoGene Therapy

Abstract: The main impediment to effective ex vivo liver gene therapy of metabolic diseases is the lack of experimental work on large animals to resolve such important issues as effective gene delivery, cell-processing techniques, and the development of appropriate vectors. We have used a nonhuman primate, as a preclinical model, to analyze the limiting steps of this approach using recombinant retroviruses. Seven monkeys (Macaca fascicularis) underwent the complete protocol: their left liver lobe was resected, a cathete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
3
22
1
3
Order By: Relevance
“…Recent improvements in oncoretroviral vector titers enabled efficient gene transfer in plated simian hepatocytes using multiple rounds of transduction before reintroduction into the animal. 22 The development of lentiviral vectors seems to have introduced a new major breakthrough in both in vivo and ex vivo liver gene therapy. 23,24 We show herewith that, using a lentiviral vector, we can bypass the critical steps of the hepatocyte ex vivo transduction procedure, namely, the plating and further deleterious trypsin dissociation of cultured hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent improvements in oncoretroviral vector titers enabled efficient gene transfer in plated simian hepatocytes using multiple rounds of transduction before reintroduction into the animal. 22 The development of lentiviral vectors seems to have introduced a new major breakthrough in both in vivo and ex vivo liver gene therapy. 23,24 We show herewith that, using a lentiviral vector, we can bypass the critical steps of the hepatocyte ex vivo transduction procedure, namely, the plating and further deleterious trypsin dissociation of cultured hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This inability to readily infect human hepatocytes was also observed with monkey hepatocytes; 1% of these cells were infected with the 3D6-Env virus, whereas up to 90% of these cells were infected with the wild-type envelope virus. 35 To determine whether the partial inhibition of the 3D6-Env virus observed on c-Met-expressing cells was due to its binding to the c-Met receptor, HuH7 were preincubated with increasing amounts of 3D6 antibodies to saturate c-Met before infection. This resulted in increased infectivity, which was correlated to the amount of 3D6 antibodies added onto the cells (Figure 5c).…”
Section: Viral Infection Of Human Primary Hepatocytes and Hepatoma Cellsmentioning
confidence: 99%
“…Recently, porcine hepatocytes have been used clinically in bioartificial livers (BAL) (13). As immune and several approaches are currently tested: (i) extracorporeal hybrid bioartificial liver devices (22,28), (ii) imresponses are still major barriers for successful cell and organ xenotransplantation, semipermeable capsules usplantable bioartificial liver devices (6,9,10), and (iii) hepatocyte transplantation (1,7,8,16,17,21,36,37,39).…”
Section: Introductionmentioning
confidence: 99%
“…The small pores of the capsules prevent Hepatocyte allotransplantation has been used successfully in rodent (16,21,37) and primates (1,39) as therapy cells and antibodies to cross, while oxygen, glucose, and nutrients can pass through the membranes and maintain of chronic or acute liver failure. In humans, studies showed that hepatocyte allotransplantation was useful metabolic functions.…”
Section: Introductionmentioning
confidence: 99%